(untitled) (African Multidisciplinary Journal of Research, 2025)
The world is grappling with a myriad of environmental challenges, key among them being climate change, marked by lasting changes in climatic patterns. Businesses have contributed significantly towards climate change by emitting greenhouse gases. Promoting employee green behaviour (EGB) is increasingly viewed as one of the effective mechanisms for reversing the adverse environmental impact of business organization. EGB refers to voluntary actions by workers in an organization that have positive impacts on the environment. One strategy proposed for developing EGB is the implementation of transformational leadership. Although literature on the link between transformational leadership and EGB exists, it is fragmented and lacks cohesion, making it difficult to draw conclusions, identify overarching principles and patterns, and pinpoint areas that need further research. This review sought to synthesize existing literature on how transformational leadership influences EGB, thereby providing clearer insights that will guide future research and practice. The review involved a comprehensive search of empirical studies using Google Scholar, employing a diverse range of synonyms related to EGB and transformational leadership. The search and appraisal processes ultimately yielded 24 relevant studies. The majority of the research focused on quantitative methodologies, with a notable concentration in Asian contexts, emphasizing the need for further exploration in diverse geographical and sectoral settings. A review of these studies revealed that transformational leadership significantly enhances EGB across various sectors by fostering organizational identification, intrinsic motivation, and providing green organizational support. Transformational leaders foster a culture of sustainability by embodying values that align organizational goals with ecological practices, thereby amplifying the motivations of employees to partake in green initiatives. Several moderating factors were identified, including organizational culture, work engagement, and employee emotional exhaustion. In conclusion, the review underscored the necessity for organizations to cultivate transformational leadership qualities to maximize employee engagement in green practices. The paper recommends implementing transformational leadership training programs for current and aspiring leaders and encourages future research to explore underrepresented sectors.